From Friends to Foe and Foe to Friends: Reconciliation Process between Taliban and The US Government in the Selected Press - Tabinda Sadiq (Journal of Peace, Development and Communication, 2023)
This study documents the reconciliation process between Taliban and the US Government to end more than two decades of conflict that stemmed from the 9/11 attacks in the USA. Over the previous two decades, the U.S. war on terror strategies has continually failed to achieve the promised results of defeating terrorism. The war brought devastating effects to the conflicting parties; consequently, both parties wanted peace negotiations. The reconciliation process took more than five years in Doha, Qatar, and finally reached an agreement in 2020 that resulted in the Taliban taking over Kabul. The study investigates the coverage of regional and international countries’ press on the reconciliation process and analyzes the content of the selected countries’ press coverage on the issue between 2015 and 2020—the peak time of the reconciliation. Results of the study exhibit that the Pakistani newspaper, Dawn, gives greater coverage to the issue, followed by the New York Times and Pajhwok Afghan, respectively. This coverage is obvious from the fact that these mentioned newspapers’ countries were the major stakeholder in the war on terror. The most widely covered topic was ‘Statements of the countries’ directly associated with the issue. The coverage also used official than private sources in covering the issues in all the countries’ press.